2000
DOI: 10.1161/01.atv.20.12.2619
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Lp(a) With a Small Apo(a) Isoform Are Associated With Coronary Artery Disease in African American and White Men

Abstract: Abstract-Elevated levels of lipoprotein(a) [Lp(a)] and the presence of small isoforms of apolipoprotein(a) [apo(a)] have been associated with coronary artery disease (CAD) in whites but not in African Americans. Because of marked race/ethnicity differences in the distribution of Lp(a) levels across apo(a) sizes, we tested the hypothesis that apo(a) isoform size determines the association between Lp(a) and CAD. We related Lp(a) levels, apo(a) isoforms, and the levels of Lp(a) associated with different apo(a) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
132
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 53 publications
13
132
3
1
Order By: Relevance
“…Wilkund et al, (1990) and Wang et al, (1990) have published data on Lp(a) level and infant and parent gene status, but the distribution of phenotypes has not yet been reported in the literature, although several studies have been carried out in other countries on white populations (Paultre et al, 2000(Paultre et al, , 2002Albers et al, 1974). The present study focuses on apo(a) phenotypes and Lp(a) concentration in a white Australian migrant population of Anglo-Celtic origin.…”
Section: Discussionmentioning
confidence: 89%
“…Wilkund et al, (1990) and Wang et al, (1990) have published data on Lp(a) level and infant and parent gene status, but the distribution of phenotypes has not yet been reported in the literature, although several studies have been carried out in other countries on white populations (Paultre et al, 2000(Paultre et al, , 2002Albers et al, 1974). The present study focuses on apo(a) phenotypes and Lp(a) concentration in a white Australian migrant population of Anglo-Celtic origin.…”
Section: Discussionmentioning
confidence: 89%
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70] It has proven more difficult to detect an association between Lp(a) and cardiovascular disease among blacks; 71,72 however, using assessment of apo(a) size allele-specific Lp(a) levels as discussed, we found an association between cardiovascular disease and Lp(a) among black and white men with small apo(a) sizes. 38 Further, the possibility that Lp(a) levels could be increased secondary to cardiovascular disease has been raised, implying that an increased Lp(a) level could be a result of disease rather than a part of the causal pathway. Studies in model systems demonstrating a stimulation of apo(a) secretion from monkey hepatocytes by interleukin (IL)-6 have provided some support for this concept.…”
Section: Cardiovascular Risk Properties: Clinical Studiesmentioning
confidence: 99%
“…38,65,114 Furthermore, although Lp(a) levels have been reported to be increased in women with myocardial infarction, 115 a recent prospective study on cerebrovascular disease demonstrated an association between Lp(a) and stroke in men but not in women. 116 This does not necessarily conflict with an association between plasma Lp(a) levels and cardiovascular disease among women, although it could suggest that any risk carried by specific apo(a) sizes may be subject to modulation by gender-specific factors.…”
Section: Berglund and Ramakrishnan Lipoprotein (A): An Elusive Cardiomentioning
confidence: 99%
See 1 more Smart Citation
“…Lp(a)'nın risk faktörü olarak değerlendirilemeye-ceği sonucu çalışma kitimizin ateroskleroz açısından daha riskli olduğu bilinen küçük boyutlu apo(a)'nın oranını saptayamamasına bağlı olabilir. Allele veya izoforma özel kitlerin kullanımının Lp(a)'nın risk faktörü olarak değerlendirilmesinde özellikle erkeklerde daha tanımlayıcı olabileceği yapılan geniş ölçekli çalışmalarda zaten ortaya çıkmış bir gerçektir 35,36 . Üçüncüsü herhangi bir risk faktörünün Framingham toplumundaki mutlak riski, diğer tüm toplumlar için geçerli olmayabilir.…”
Section: Gereç Ve Yöntemunclassified